Propuesta de mejoramiento para la disminución de desperdicios mediante Lean Manufacturing en una PYME del sector alimenticio (2021)
Los Dulces de Samy is an SME that competes in the Food sector. As it is such a competitive market, it is very important to have advantages that allow the company to differentiate itself from the competitors, among them price strategies are included. In search of this advantage, it is necessary to increase the production capacity of the confectionery through the improvement of the processes, turning them into more efficient activities and reducing the waste that is presented. The Lean Manufacturing philosophy offers tools that allow attacking this problem, helping companies to identify shortcomings and thus improve production processes. This is how this work proposes the use of Lean tools applied in the SME Los Dulces de Samy. Initially, an analysis of the tools is made and it is found that it is very important to make a diagnosis of the company and that before implementing Lean tools, the 5's that are the pillar to be able to apply this philosophy in the company must be implemented. In this way, a diagnosis of the company is presented and the productive problems it has are identified. Later, a Pareto diagram is made in which it is concluded that the product that generates greater impact to the company are the alfajores on which an analysis of processes is made, to finally present a proposal of continuous improvement of the identified factors. It is concluded that it is necessary to use a manual of good practices and the implementation of other Lean tools such as KANBAN and PHVA in the process to improve productivity